Features of platforms used in online teaching English at universities (Journal of Educational Sciences, 2021)
All the methods and techniques used throughout the development of teaching English in higher edu- cation have been dependent on technical equipments. Later, in addition to them, various new innovative technologies appeared. L.N. Gumilyov Eurasian National University has a long history of using various learning platforms in English lessons. However, due to the global coronavirus pandemic, compulsory online learning has presented a different challenge for teachers, which resulted in the acquisition of other new knowledge and skills. In a short time, it was necessary to master the features of online learning, so as not to reduce the quality of lessons and students’ interest in the subject. Therefore, the teachers ac- tively participated in national and international seminars organized by the university. The use of various programs in online learning affects the teacher’s approach and improves the quality of the lessons. This article analyzes the online platforms used by teachers and discusses their advantages and disadvantages. In addition, the concepts of “distance learning”, “online learning”, “online platforms” were defined. A survey was conducted among the teachers of L. Gulilyov ENU. The survey results showed how com- petently university teachers can use online platforms and what parameters to pay attention to when choosing them.Key words: online learning, distance learning, learning platforms, English learning, platform parameters.